THE POWER STRUCTURE OF UNDERGROUND ECONOMY ACTIVITIES AT ROMBENGAN MALAM KOTA MALANG: AN INSTITUTIONAL ECONOMIC PERSPECTIVE - Fitrian Aprilianto (Universitas Padjadjaran, 2023)
One of Indonesia’s most common underground economy practices is the emergence of informal markets in the community. This study aimed to identify the pattern of the power structure of the Roma merchants in Malang City from an institutional economic perspective. In this study, the method used is a descriptive qualitative approach with a phenomenological type. This study uses primary data, data directly obtained from interviews and observations. The main informants in the study were traders, and the supporting informants were parking attendants. From the researchers’ findings, it was found that several realities of the power structure existed until now, among others, in the Roma merchant community, there was no hierarchical and formal pattern of power structures that officially governed the merchant community. Mastery in the Roma community was only informal.